PENGARUH LITERASI KEUANGAN, KONTROL DIRI, DAN PERILAKU KONSUMTIF TERHADAP KONSUMSI MERCHANDISE K-POP BAGI MAHASISWA GENERASI Z MENJADI K-POPERS DI UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Setiyorini, Atik; Yudiantoro, Deny (CV. Lafadz Jaya, 2025)
The phenomenon of K-Pop idols from South Korea, known as Hallyu or the Korean Wave, has widely spread to Indonesia. This culture is highly favored by the community, especially Generation Z, who actively follow trends, including the consumption of K-Pop merchandise. This study aims to examine the influence of financial literacy, self-control, and consumer behavior on K-Pop merchandise consumption among Generation Z students at UIN Sayyid Ali Rahmatullah Tulungagung. The research method used is quantitative, with questionnaires distributed via Google Forms to 116 respondents. The data were analyzed using SPSS 29 through validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results indicate that financial literacy has a significant effect on K-Pop merchandise consumption, while self-control and consumer behavior have a positive but not statistically significant partial effect. Simultaneously, these three variables have a significant influence on merchandise consumption.